Transcriptomic integration of D4R and MOR signaling in the rat caudate putamen - Alejandra Valderrama-Carvajal (Nature Portfolio, 2018)
Abstract Morphine binding to opioid receptors, mainly to μ opioid receptor (MOR), induces alterations in intracellular pathways essential to the initial development of addiction. The activation of the dopamine D4 receptor (D4R), which is expressed in the caudate putamen (CPu), mainly counteracts morphine-induced alterations in several molecular networks. These involve transcription factors, adaptive changes of MOR signaling, activation of the nigrostriatal dopamine pathway and behavioural effects, underlining functional D4R/MOR interactions. To shed light on the molecular mechanisms implicated, we evaluated the transcriptome alterations following acute administration of morphine and/or PD168,077 (D4R agonist) using whole-genome microarrays and a linear regression-based differential expression analysis. The results highlight the development of a unique transcriptional signature following the co-administration of both drugs that reflects a countereffect of PD168,077 on morphine effects. A KEGG pathway enrichment analysis using GSEA identified 3 pathways enriched positively in morphine vs control and negatively in morphine + PD168,077 vs morphine (Ribosome, Complement and Coagulation Cascades, Systemic Lupus Erythematosus) and 3 pathways with the opposite enrichment pattern (Alzheimer’s Disease, Neuroactive Ligand Receptor Interaction, Oxidative Phosphorilation). This work supports the massive D4R/MOR functional integration at the CPu and provides a gateway to further studies on the use of D4R drugs to modulate morphine-induced effects.